Cycling before and after Exhaustion Differently Affects Cardiac Autonomic Control during Heart Rate Matched Exercise - Weippert, Matthias; Behrens, Martin; Mau-Moeller, Anett; Bruhn, Sven; Behrens, Kristin (Frontiers in Physiology, 2017)
During cycling before (PRE) and after exhaustion (POST) different modes of autonomic cardiac control might occur due to different interoceptive input and altered influences from higher brain centers. We hypothesized that HR variability (HRV) is significantly affected by an interaction of the experimental period (PRE vs. POST) and exercise intensity (HIGH vs. LOW; HIGH = HR > HR at the lactate threshold (HRLT), LOW = HR ≤ HRLT) despite identical average HR. Methods: 50 healthy volunteers completed an incremental cycling test until exhaustion. Workload started with 30 W at a constant pedaling rate (60 rpm) and was gradually increased by 30 W ∙ 5 min-1. Five adjacent 60 s inter-beat (R-R) interval segments from the immediate recovery period (POST 1 – 5 at 30 W and 60 rpm) were each matched with their HR-corresponding 60 s segments during the cycle test (PRE 1 – 5). An analysis of covariance was carried out with one repeated-measures factor (PRE vs. POST exhaustion), one between-subject factor (HIGH vs. LOW intensity) and respiration rate as covariate to test for significant effects (p < 0.050) on the natural log-transformed root mean square of successive differences between adjacent R-R intervals (lnRMSSD60s). Results: LnRMSSD60s was significantly affected by the interaction of experimental period × intensity (F(1;242) = 30.233, p < 0.001, ŋp2 = 0.111). LnRMSSD60s was higher during PRE compared to POST at LOW intensity (1.6 ± 0.6 ms vs. 1.4 ± 0.6 ms; p < 0.001). In contrast, at HIGH, lnRMSSD60s was lower during PRE compared to POST (1.0 ± 0.4 ms vs. 1.2 ± 0.4 ms; p < 0.001). Conclusion: Identical net HR during cycling can result from distinct autonomic modulation patterns. Results suggest a pronounced sympathetic-parasympathetic coactivation immediately after the cessation of peak workload compared to HR-matched cycling before exhaustion at HIGH intensity. On the opposite, at LOW intensity cycling, a stronger coactivational cardiac autonomic modulation pattern occurs during PRE-exhaustion if compared to POST-exhaustion cycling. The different autonomic modes during these phases might be the result of different afferent and/or central inputs to the cardiovascular control centers in the brainstem.